Lawyers as Guardians of Justice (officer of the court) : A Normative and Practical Review of the Indonesian Legal System - Saepudin, Acep (Milthree Law Journal, 2025)
This study discusses the existence and role of advocates as officers of the court in the Indonesian legal system. In law enforcement practice, advocates have a strategic position as part of law enforcement that serves to maintain a balance between the legal interests of the state, society, and those seeking justice. However, in reality, various problems are still found, such as professional ethical violations, commercialization of legal services, and weak commitment of advocates to the values of justice and judicial integrity. These conditions pose challenges for the legal profession to reaffirm its function as a profession that is free, independent, and responsible for upholding justice. This study uses a normative juridical method with a regulatory approach and conceptual analysis of the practice of the legal profession in Indonesia. The purpose of this study is to analyze the role of lawyers as law enforcers and guardians of judicial morality, as well as to evaluate the application of the principle of officer of the court in maintaining the spirit of justice. The results of the study show that lawyers exist not only as litigants, but also as guardians of substantive justice, which is a key pillar of the Indonesian legal system